Implementasi Metode AHP Pada Sistem Pendukung Keputusan Gaji Bonus Karyawan di PT Sadhana Adiwidya Bhuana - I Made Rian Wijaya; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
PT Sadhana Adiwidya Bhuana is a company engaged in business and management consulting services which still applies manual methods in giving employee salary bonuses. To develop a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to determine the weight criteria. There are eight criteria used in employee assessment, including Key Performance Indicators (KPI), Data Analysis, Critical Thinking, Creative and Innovative, Communication, Cooperation, Attitude, and Attendance. Then the award is given in four forms, namely less, sufficient, good, and very good, with scores of 1, 2, 3, and 4. The results of the weighting of the criteria with the AHP method obtained key performance indicators (KPI) scores 0.330, data analysis score 0.183, critical thinking score 0.125, creative and innovative score 0.119, communication score 0.111, cooperation score 0.063, attitude score 0.034, and attendance score 0.031. The weight will be a reference in calculating the performance score of the employee who will determine the bonus salary. This system has been tested using blackbox testing, with the test results being appropriate.